Language Learning in Higher Education : Journal of the European Confederation of Language Centres in Higher Education (CercleS) (De Gruyter Mouton, 2011)
Language Learning in Higher Education, the journal of the European Confederation of Language Centres in Higher Education, deals with the most relevant aspects of language acquisition at university. It publishes contributions presenting the outcomes of research on language teaching, blended learning and autonomous learning, and language assessment, as well as aspects of professional development, quality assurance and university language policy.